Unusual cause of parietal thoracic pain: A case report - Labied, Mohamed; Lhajoui, Hayat; Touil, Najwa; Kacimi, Omar; Chikhaoui, Nabil (Archives of Case Reports, 2020)
We report the radio-clinical observation of a 21-year-old patient, referred for anterior chest parietal discomfort evolving for 3 months ago, with the notion of trauma. The chest CT (computed tomography) scan detected a costal cartilage fracture without associated traumatic pulmonary or mediastinal changes. This case illustrates the usefulness of imaging in the diagnosis and management of costal cartilage fractures, and for screening out differential diagnoses. The aim of this study is to determine the interest of imaging in the study of fractures of the chrondro-costal cartilage. Is to determine the CT value in chrondro-costal cartilage fracture.